Chronicity factors of temporomandibular disorders: a critical review of the literature - Maísa Soares GUI; Célia Marisa RIZZATTI-BARBOSA (Sociedade Brasileira de Pesquisa Odontológica, 2015)
Facial pain often persists long after any identifiable organic pathology has healed. Moreover, in a subgroup of patients with temporomandibular disorder (TMD), no treatment is effective. Knowledge of factors associated with persistent pain in TMD could help identify personalized treatment approaches. Therefore, we conducted a critical review of the literature for the period from January 2000 to December 2013 to identify factors related to TMD development and persistence. The literature findings showed that chronic TMD is marked by psychological distress (somatization and depression, affective distress, fear of pain, fear of movement, and catastrophizing) and characteristics of pain amplification (hyperalgesia and allodynia). Furthermore, these factors seem to interact in TMD development. In addition, our review demonstrates that upregulation of the serotonergic pathway, sleep problems, and gene polymorphisms influence the chronicity of TMD. We conclude that psychological distress and pain amplification contribute to chronic TMD development, and that interactions among these factors complicate pain management. These findings emphasize the importance of multidisciplinary assistance in TMD treatment.